Skin-friction drag reduction in a channel flow with streamwise-aligned plasma actuators - Mahfoze,O; Laizet,S (International Journal of Heat and Fluid Flow, 2017)
Direct Numerical Simulations in a turbulent channel flow at a moderate Reynolds number are performed in order to investigate the potential of Dielectric Barrier Discharge (DBD) plasma actuators for the reduction of the skin-friction drag. The idea is to use a sparse array of streamwise-aligned plasma actuators to produce near-wall spanwise-orientated jets in order to destroy the events which transport high-speed fluid towards the wall. It is shown that it is possible to reduce the drag by about 33.5% when the streamwise-aligned actuators are configured to generate appropriate spanwise-orientated jets very close to the wall so that the sweeps which are mainly responsible for the skin-friction are destroyed. We demonstrate that it is possible to achieve significant drag reduction with a sparse array of streamwise-aligned plasma actuators, with one order of magnitude less actuators than previous experiments in a similar set-up.